Up-regulation of LCN2 in the anterior cingulate cortex contributes to neural injury-induced chronic pain - Song, Xiang-Jie; Yang, Chen-Ling; Chen, Danyang; Yang, Yumeng; Mao, Yu; Cao, Peng; Jiang, Aijun; Wang, Wei; Zhang, Zhi; Tao, Wenjuan (Frontiers in Cellular Neuroscience, 2023)
Chronic pain caused by disease or injury affects more than 30% of the general population. The molecular and cellular mechanisms underpinning the development of chronic pain remain unclear, resulting in scant effective treatments. Here, we combined electrophysiological recording, in vivo two-photon (2P) calcium imaging, fiber photometry, Western blotting, and chemogenetic methods to define a role for the secreted pro-inflammatory factor, Lipocalin-2 (LCN2), in chronic pain development in mice with spared nerve injury (SNI). We found that LCN2 expression was upregulated in the anterior cingulate cortex (ACC) at 14 days after SNI, resulting in hyperactivity of ACC glutamatergic neurons (ACCGlu) and pain sensitization. By contrast, suppressing LCN2 protein levels in the ACC with viral constructs or exogenous application of neutralizing antibodies leads to significant attenuation of chronic pain by preventing ACCGlu neuronal hyperactivity in SNI 2W mice. In addition, administering purified recombinant LCN2 protein in the ACC could induce pain sensitization by inducing ACCGlu neuronal hyperactivity in naïve mice. This study provides a mechanism by which LCN2-mediated hyperactivity of ACCGlu neurons contributes to pain sensitization, and reveals a new potential target for treating chronic pain.